Economical Assessment of Working Memory and Response Inhibition in ADHD Using a Combined n-back/Nogo Paradigm: An ERP Study - Breitling-Ziegler, Carolin; Tegelbeckers, Jana; Flechtner, Hans-Henning; Krauel, Kerstin (Frontiers in Human Neuroscience, 2020)
The development of cognitive interventions in ADHD often requires the assessment of multiple cognitive functions. However, experimental settings consisting of various tasks are particularly strenuous for patients and can thus result in poor data quality. For the economical assessment of working memory and response inhibition, this study aims to validate a combined n-back/nogo paradigm by comparing it to single task versions and to demonstrate its applicability for ADHD research. Twenty-five healthy individuals and 34 ADHD patients between 9 and 16 years participated in this ERP study. Healthy controls underwent single task versions of a 2-back working memory task and a go/nogo response inhibition task as well as the introduced combined 2-back/nogo task. This combined task demonstrated a comparable ERP structure for working memory and response inhibition aspects as single task versions. Behaviorally, higher working memory performance during the combined paradigm indicated lower task difficulty, while high correlations between combined and single task versions still indicated valid working memory measures. For response inhibition performance, different task versions resulted in similar outcomes. The application of the combined n-back/nogo paradigm in ADHD patients revealed the expected working memory and response inhibition deficits, increased omission errors, reaction times, and standard deviation of reaction time, as well as diminished n-back P3 and nogo P3 amplitudes. We conclude that the combined n-back/nogo task is an effective paradigm for the economical assessment of working memory and response inhibition deficits in ADHD on a behavioral and neurophysiological level.